2007
DOI: 10.1021/jp0677703
|View full text |Cite
|
Sign up to set email alerts
|

N-Nitrosation of Amines by NO2 and NO:  A Theoretical Study

Abstract: Gas-phase nitrosation of amines implies a nonionic pathway different from the nitrosonium nitrosation via acidification of nitrite. Electronic structure calculations discussed in this work suggest a free radical mechanism, in which NO2 abstracts a hydrogen atom from the nitrogen in primary and secondary amines to form an intermediate complex of an aminyl radical and nitrous acid. The aminyl radical intermediate is then quenched by nitric oxide, leading to the formation of nitrosamine. High-level calculations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 23 publications
2
35
0
1
Order By: Relevance
“…7 and Table 2). The enthalpy of activation (Δ H ‡ = 41 ± 2 kJ/mol) and activation energy ( E a = 43 ± 2 kJ/mol) indicate a relatively low activation barrier for the reaction and are consistent with values obtained from other experimental and theoretical examinations of nitrosation of secondary amines 3941. The negative entropy of activation (Δ S ‡ = −120 ± 10 J/mol·K) is consistent with an associative nitrosation mechanism.…”
Section: Resultssupporting
confidence: 86%
“…7 and Table 2). The enthalpy of activation (Δ H ‡ = 41 ± 2 kJ/mol) and activation energy ( E a = 43 ± 2 kJ/mol) indicate a relatively low activation barrier for the reaction and are consistent with values obtained from other experimental and theoretical examinations of nitrosation of secondary amines 3941. The negative entropy of activation (Δ S ‡ = −120 ± 10 J/mol·K) is consistent with an associative nitrosation mechanism.…”
Section: Resultssupporting
confidence: 86%
“…3). Also, the order of reactivity for heterocyclic amines follows the increase in the ring size (the similar was found in the case of N‐nitrosation of heterocyclic amines) 43. For example, seven‐membered azepine, having GB = 923.5 kJ mol −1 , is more reactive than four‐membered ring azetidine, which has GB = 908.6 kJ mol −1 .…”
Section: Methodssupporting
confidence: 58%
“…This behavior is supported by atomic ratios calculated from XPS data, where it is shown that nitrogen associated with the amine group is actually reduced compared to the baseline material. The amine group may also be responsible for forming complexes with NO 2 and any NO generated by other reactions, such as interaction with water …”
Section: Figurementioning
confidence: 99%